2015
DOI: 10.3329/jbs.v21i0.22524
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Bacteria and their drug susceptibility pattern in children to establish the correlation between childhood Septicemia with C-reactive protein (CRP) levels

Abstract: Context: Neonatal sepsis is one of the most important causes of morbidity and mortality and C-reactive protein (CRP) an excellent biomarker has significant diagnostic and prognostic value for the treatment of septicemia patient. Objectives: To isolate and identify viable pathogens from blood culture and their antibiogram and to correlate CRP levels with septicemic child. Materials and Methods: A total of 273 cases among which 233 were clinically suspected septicemia cases and 40 were healthy controls in age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Kasahun et al, [30] recorded 92.5 percent in Ethiopia, and Kiran et al, [15] reported 84.6 percent in India. However, Dhakar [31] and Saudi Arabia [8] research indicated 74% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Kasahun et al, [30] recorded 92.5 percent in Ethiopia, and Kiran et al, [15] reported 84.6 percent in India. However, Dhakar [31] and Saudi Arabia [8] research indicated 74% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 91%